Beyond Solid Solution High‐Entropy Alloys: Tailoring Magnetic Properties via Spinodal Decomposition. (9th November 2020) - Rao, Ziyuan; Dutta, Biswanath; Körmann, Fritz; Lu, Wenjun; Zhou, Xuyang; Liu, Chang; da Silva, Alisson Kwiatkowski; Wiedwald, Ulf; Spasova, Marina; Farle, Michael; Ponge, Dirk; Gault, Baptiste; et al.
Abstract: Since its first emergence in 2004, the high‐entropy alloy (HEA) concept has aimed at stabilizing single‐ or dual‐phase multi‐element solid solutions through high mixing entropy. Here, this strategy is changed and renders such massive solid solutions metastable, to trigger spinodal decomposition for improving the alloys' magnetic properties. The motivation for starting from a HEA for this approach is to provide the chemical degrees of freedom required to tailor spinodal behavior using multiple components. The key idea is to form Fe‐Co enriched regions which have an expanded volume (relative to unconstrained Fe‐Co), due to coherency constraints imposed by the surrounding HEA matrix. As demonstrated by theory and experiments, this leads to improved magnetic properties of the decomposed alloy relative to the original solid solution matrix. In a prototype magnetic FeCoNiMnCu HEA, it is shown that the modulated structures, achieved by spinodal decomposition, lead to an increase of the Curie temperature by 48% and a simultaneous increase of magnetization by 70% at ambient temperature as compared to the homogenized single‐phase reference alloy. The findings thus open a pathway for the development of advanced functional HEAs. Abstract : A novel strategy for improving magnetic properties of high‐entropy alloys (HEAs) is demonstrated in a prototype magnetic FeCoNiMnCu HEA by triggering bulk spinodal decomposition based on both theory and experiments. The key idea is to form Fe‐Co enriched regions which have an expanded volume (relative to unconstrained Fe‐Co), due to coherency constraints imposed by the surrounding HEA matrix.